Simple synthesis of 2-amino-4-(het)aryl-4,6-dihydro-1(3)(11)H-[1,3,5]triazino[2,1-b]quinazolin-6-ones - Dolzhenko, Anton; Dolzhenko, A.; Chui, W. (HeteroCorporation and John Wiley & Sons, 2008)
The 2-amino-4-(het)aryl-4,6-dihydro-1(3)(11)H-[1,3,5]triazino[2,1-b]quinazolin-6-ones were prepared readily by cyclocondensation of anthranilic acid derived 4-oxo-3,4-dihydroquinazolinyl-2-guanidine with a variety of aldehydes. The structures of the compounds were confirmed by nmr spectroscopy, including 2D NOESY experiments.